Oncostatin M receptor-dependent signaling assessed by RNA sequencing in mouse hematopoietic stem cells - Logan S. Schwartz; Ruth L. Saxl; Tim Stearns; Maria Telpoukhovskaia; Jennifer J. Trowbridge (Scientific Data, 2024)
Abstract Oncostatin M (OSM) is a member of the interleukin-6 (IL-6) family of cytokines and has been found to have anti-inflammatory and pro-inflammatory properties in various cellular and disease contexts. OSM signals through two receptor complexes, one of which includes OSMRβ. Here, we investigated OSM-OSMRβ signaling in adult mouse hematopoietic stem cells (HSCs) using the conditional Osmr fl/fl mouse model B6;129-Osmr tm1.1Nat /J. We crossed Osmr fl/fl mice to interferon-inducible Mx1-Cre, which is robustly induced in adult HSCs. From these mice, we isolated HSCs by flow cytometry, stimulated with recombinant OSM or vehicle for 1 hour, and assessed gene expression changes in control versus Osmr knockout HSCs by RNA-seq. This data may be utilized to investigate OSMRβ -dependent and -independent OSM signaling as well as the transcriptional effects of an IL-6 family cytokine on mouse HSCs to further define its anti-inflammatory versus pro-inflammatory properties.